Two new cave-dwelling pseudoscorpions (Pseudoscorpiones: Neobisiidae: Parobisium) from Yunnan, China - Zhang, Chen; Feng, Zegang; Zhang, Feng (Zootaxa, 2020)
Two new species of troglomorphic pseudoscorpions of the family Neobisiidae, collected from karst caves in Yunnan, China, are described: Parobisium laevigatum sp. n. and P. muchonggouense sp. n.. A key to the Parobisium species from China is also provided.